Análisis, diseño e implementación de un sistema de gestión administrativo y académico para el "Instituto de Idiomas" de la Universidad Técnica de Machala integrado al SIUTMACH - Zhimineycela Tenecela, Ramiro Bladimir (2014)
In the following study the technical feasibility of designing and implementing a system of administrative and academic language for the Institute of the Technical University of Machala management was analyzed.